AI narratives - Cave, Stephen,Dihal, Kanta,Dillon, Sarah (New York, NY, 2020)
This book is the first to examine the history of imaginative thinking about intelligent machines, featuring contributions from leading humanities and social science scholars who detail the narratives about artificial intelligence (AI) that in turn offer a crucial epistemic site for exploring contemporary debates about these powerful technologies
9780198846666
Keywords: Aufsatzsammlung